The potential of Black Garlic as Livestock Feed Supplement - Mayulu, Hamdi; Sawitri, Endang (Technium BioChemMed, 2023)
Black garlic is generated from the fermentation of the fresh ones in one to three weeks at 60-80oC and relative humidity of 50-99%. This product is derived without additives and is utilized for human or livestock health. In general, it contains bioactive substances, including Antioxidants, Polyphenols, Gallic, Chlorogenic, Caffeic, P-Coumaric Acid, and Flavonoid. These substances can be used as prebiotics and feed supplements for livestock, especially small ruminants. Feed supplements are an alternative solution to promote healthy, economic, and environmentally friendly livestock production, productivity, and performance. Furthermore, healthy livestock implies safe and healthy food production for humans.